THE EXTERNAL CONFLICTS OF EMMA IN EMMA MOVIE (2020) - Puspita, Gabriela Novena; Gemilang, Adria Vitalya; Hikmah, Isti'anatul (Rubikon : Journal of Transnational American Studies, 2024)
The purpose of this study is about to find the external conflict in Emma movie (2020). Emma movie (2020) directed by Autumn de Wilde and was adapted from the novel by Jane Austen (1815) that had the same name. The movie showed the relations between Emma and the other character and sometimes there were conflicts between them. There are two objectives of this study: 1) to analyse the external conflicts between the main character (Emma) and the other characters in Emma movie (2020) that can be reflected in conversation in the movie and the movie script; 2) to find out the solution of the external conflicts that occurred in Emma movie (2020) that is shown in conversation in the movie and the movie script. In collecting the data from the movie, the researcher used qualitative research in analysing the data. The researcher used the external conflict theory by William Kenny (1966) and the conflict management strategies by Deetz and Stevenson (1986) to analyse the data. This research found six external conflicts experienced by the main character Emma and four data from the conflict management strategies. The findings of this research taught that there are several ways to resolve the conflicts until it reaches an agreement between both sides.